Improving Developmental Screening and Supporting Families with Paid Parent Partners. Issue 1 (January 2023) - Badawi, Debbie G.; Thomas, Josie; Archuleta, Pattie; Taylor, Stacy; Pyle, Meredith
Abstract : This article presents the results of a unique effort to improve developmental screening follow-up using paid parent partners integrated into primary care practices. Abstract: Objective: The primary goals of the project were to improve rates of developmental screening and appropriate referral for atypical screens for children from birth to 3 years in participating practices and to integrate parent partners (PPs) into primary care. Method: Parents' Place of Maryland, in collaboration with the Maryland Department of Health, developed a quality improvement project to improve rates of developmental screening, referral, and follow-up. Nine practices from across the state completed the project. Participating practices received training and technical assistance for screening, referral, and data collection as well as a paid part-time PP to assist with care coordination. Families of children with atypical developmental screening results were offered a referral to receive support in following through with referrals, including needed social services to address health care barriers. Results: Developmental screening rates across practices increased from 65% to 95% during the 9-month project, and autism-specific screening increased from 75% to 94%. Appropriate referral rates tripled from 6% to 20% of children. After an initial learning curve, practices gradually increased referrals to PPs, and they served 292 individual families (total of 544 contacts) over 9 months. PPs helped families identify a variety of community services to meet their needs. Conclusion: While developmental screening rates can be improved using quality improvement processes, supporting families to connect to services requires additional resources. Integrating trained PPs into pediatric practices improves access to community-based services in a cost-efficient manner. More research is needed to identify the most efficient models for providing this service on a broader scale.